Academic Hope and its Relationship to the Motivation of Learning among Al-Balqa Applied University Students - Ahmed Al-Alwan; Omar Al-Adamat; Emad Al-Zubi (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at investigatng the level of academic hope and its relation to learning motivation among university students according to their gender and specialization. The sample consisted of (640) students who were studying at Al- Balqa' Applied University. To achieve the study aims, academic hope scale and learning motivation scales were used. The study results revealed that the level of academic hope among university students was high. Moreover, the results showed that there were  statistically significant differences in level of academic hope attributed to gender in favour of female students and in specialization in favour of scientific specializations. Finally,  the study results revealed that there was a statistically significant correlation between academic hope and learning motivation.